Thermochemistry and kinetics of the 2‐butanone‐4‐yl CH3C(=O)CH2CH2 + O2 reaction system. Issue 8 (3rd May 2019) - Sebbar, N.; Bozzelli, J. W.; Trimis, D.; Bockhorn, H.
Abstract: Thermochemistry and kinetic pathways on the 2‐butanone‐4‐yl (CH3 C(=O)CH2 CH2 ) + O2 reaction system are determined. Standard enthalpies, entropies, and heat capacities are evaluated using the G3MP2B3, G3, G3MP3, CBS‐QB3 ab initio methods, and the B3LYP/6‐311g(d, p) density functional calculation method. The CH3 C(=O)CH2 CH2 radical + O2 association reaction forms a chemically activated peroxy radical with 35 kcal mol −1 excess of energy. The chemically activated adduct can undergo RO−O bond dissociation, rearrangement via intramolecular hydrogen transfer reactions to form hydroperoxide‐alkyl radicals, or eliminate HO2 and OH. The hydroperoxide‐alkyl radical intermediates can undergo further reactions forming ketones, cyclic ethers, OH radicals, ketene, formaldehyde, or oxiranes. A relatively new path showing a low barrier and resulting in reactive product sets involves peroxy radical attack on a carbonyl carbon atom in a cyclic transition state structure. It is shown to be important in ketones when the cyclic transition state has five or more central atoms.